2018
DOI: 10.31426/ijamsr.2018.1.7.718
|View full text |Cite
|
Sign up to set email alerts
|

A Study On Work-Life Balance In Working Women

Abstract: The purpose of working women has changed throughout the creation due to economic shifts and social needs. This has resulted in a scenario in which working women have tremendous pressure to develop a career as robust as their male counterparts while nourishing active engagement in personal life. The ever-increasing workload is bringing a plaster bandage on the working women leaving them with less time for themselves. The increasing responsibilities on the personal front with the technological blessings like adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…The work environments are highly competitive, and employees that wish to give their best to everything find WLB as an impossible goal (Tummala, 2016). Though the academic community enjoys the privileges of leave or semester/year breaks, work stress among faculty of higher education programs is reported in studies (Beddoes & Pawley, 2014;Delina & Raya, 2013;Lakshmi & Prasanth, 2018;Ren & Caudle, 2016). Work stress was related to WLB, and higher levels of work stress were reported among women than men in the education sector (Lakshmi & Prasanth, 2018;Muben & Karim, 2018;Senthilkumar et al, 2012;Slišković & Maslić Seršić, 2011;Tummala, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The work environments are highly competitive, and employees that wish to give their best to everything find WLB as an impossible goal (Tummala, 2016). Though the academic community enjoys the privileges of leave or semester/year breaks, work stress among faculty of higher education programs is reported in studies (Beddoes & Pawley, 2014;Delina & Raya, 2013;Lakshmi & Prasanth, 2018;Ren & Caudle, 2016). Work stress was related to WLB, and higher levels of work stress were reported among women than men in the education sector (Lakshmi & Prasanth, 2018;Muben & Karim, 2018;Senthilkumar et al, 2012;Slišković & Maslić Seršić, 2011;Tummala, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Though the academic community enjoys the privileges of leave or semester/year breaks, work stress among faculty of higher education programs is reported in studies (Beddoes & Pawley, 2014;Delina & Raya, 2013;Lakshmi & Prasanth, 2018;Ren & Caudle, 2016). Work stress was related to WLB, and higher levels of work stress were reported among women than men in the education sector (Lakshmi & Prasanth, 2018;Muben & Karim, 2018;Senthilkumar et al, 2012;Slišković & Maslić Seršić, 2011;Tummala, 2016). Owens et al (2018) in their review highlight the lack of personal time, self-imposed expectations, committee work, research and publishing demands, institutional procedures, and colleagues as the sources of academic stress.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Because of the intense competition in the workplace, people who want to give it their all perceive work-life balance as an unachievable ideal (Tummala, 2016). Studies have shown that professors in programmes of higher education institutions experience work stress, despite the academic community's benefits such as vacation leaves and semester/year breaks (Lakshmi & Prasanth, 2018;Ren & Caudle, 2016). Furthermore, a correlation has been found between workplace stress and work-life balance (WLB), wherein women in the education sector report higher levels of work-related stress compared to men (Lakshmi & Prasanth, 2018;Muben & Karim, 2018;Tummala, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Tamil Nadu, there are nearly 59 Universities which are approved by the UGC and are run under the direction of Ministry for Higher Education development, these universities are mainly classified into central, state and deemed. It has been widely stated that the work life balance is perceived to be better in the education sector, however the sad part is that it is not entirely true (Lakshmi 2018). Researchers has identified that the professors and faculty members in colleges and universities tend to face considerable amount of pressure at work from handling the classes, preparation for class, record keeping, publishing research articles, preparation of project reports, book publishing, adhering to the standards as set by UGC, NAAC and other regulatory bodies.…”
Section: Introductionmentioning
confidence: 99%